Komunikasi Persuasif pada Pendidikan Anak - Triwardhani, Ike Junita (FIkom Unisba, 2006)
There are two assumptions describing children learning process. First assumption theorized by France philosopher Jean Jacques Rousseau emphasized on the importance of children to return to nature. By learning in its natural space, Rousseau believed that children would achieve its peak performance in learning. The second assumption promoted by modern education experts such as Maria Montessori justified learning process more than learning space. For them, wherever children learn, one must attended the process of learning seriously. They believed that learning process would reach maximum impact if children learn in a state of playful mind. By nature, children love to play, and they learn through their play. Whatever theory picked up by educators, this article discussed the importance of persuasive communication on children learning process. Persuasive communication enabled children to develop creative mind which serve best to express themselves or to solve their problems.